Pseudomorphic replacement of diopside during interaction with (Ni,Mg)Cl2 aqueous solutions: Implications for the Ni-enrichment mechanism in talc- and serpentine-type phases - Majumdar, A.; King, H.; John, T.; Kusebauch, C.; Putnis, Andrew (Elsevier Science BV, 2014)
A hydrothermal experimental study of diopside interaction with (Ni,Mg)Cl2 aqueous solutions has been carried out to clarify the replacement mechanism and pattern of element mobilization and its relevance to peridotite alteration. Three different solution compositions were used with Ni/Mg ratios of 0, 0.5, and 1, respectively. Experiments were carried out in cold-seal pressure-vessels at 300–600 °C and 100 MPa pressure for 15 days in gold capsules. For 600 °C NiCl2 experiments, the solutions were also spiked with 50% H218O to study the behavior of isotopic exchange and hence the replacement mechanism. The diopside–pseudomorph interface is compositionally and structurally sharp. After the MgCl2 experiments pure talc and/or serpentine comprised the replacement phases, whereas reaction in the Ni-bearing fluids produced talc–willemseite and/or lizardite–nepouite series compositions. Additionally, a complex rim of Ni-poor and Ni-rich regions developed in the NiCl2 and (Ni,Mg)Cl2 experiments. Raman spectroscopy of the Ni-rich talc from the experiment with 18O-enriched solution showed a shift of ~ 10 ± 1 cm− 1 for the Sisingle bondO(bridging)single bondSi band towards lower wavenumbers relative to unspiked solution experiments, indicating that 18O was incorporated into the silicate framework; thus the reaction progressed via an interface-coupled dissolution-precipitation mechanism.Overgrowths of an olivine-type phase at 500–600 °C and serpentine-type phases in 300–400 °C experiments were also observed. For a simple binary composition (e.g. Ni–Mg) of the interacting solution, the fluid composition (different Ni/Mg ratio) at the reacting interface and its silica activity has a strong control on the phase precipitated. The sequential formation of a Ni-poor inner phase and Ni-rich outer phase indicates a stepwise increase in Ni incorporation within the neo-formed phase that is representative of a cyclic dissolution-precipitation process during supergene enrichment of Ni in natural ore deposits. Additionally, Ca transport occurs in the opposite direction to Ni during alteration, which may be important as a geochemical tracer for economic Ni-deposits and as a source of Ca for the rodingitization processes that are often associated with peridotite occurrences.